1989
DOI: 10.1111/j.1365-2125.1989.tb05410.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of two antimycotic agents, ketoconazole and terbinafine on the metabolism of tolbutamide, ethinyloestradiol, cyclosporin and ethoxycoumarin by human liver microsomes in vitro.

Abstract: Two antimycotic agents, the azole ketoconazole and the allylamine terbinafine, have been examined for their effects on the metabolism of tolbutamide, ethinyloestradiol, cyclosporin and ethoxycoumarin by human liver microsomes (n = 4) in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…In vitro terbinafine did not inhibit cyclosporin metabolism, confirming the results of a previous study (Back et al, 1989). The novel structure of terbinafine precludes binding to known cytochrome P450 isoenzymes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In vitro terbinafine did not inhibit cyclosporin metabolism, confirming the results of a previous study (Back et al, 1989). The novel structure of terbinafine precludes binding to known cytochrome P450 isoenzymes.…”
Section: Discussionsupporting
confidence: 79%
“…Cyclosporin hydroxylase activity was determined as described previously (Back et al, 1989), with the following modifications: Incubations contained cyclosporin (CsA; 5 JIM, [3H]-CsA; 0.1 ,uCi, a gift from Sandoz Pharmaceuticals, Basle), and microsomal protein (1.5 mg) and were performed in 10 ml wide neck glass tubes at 370 C with agitation for 20 min. Other reaction constituents and the extraction procedure remained unchanged.…”
Section: (1951)mentioning
confidence: 99%
See 1 more Smart Citation
“…69 For drugs that are not substrates of CYP2D6 (eg, anticoagulants, corticosteroids, oral contraceptives, tolbutamide, cyclosporine, midazolam, digoxin and terfenadine) terbinafi ne has only a modest or minimal affect on their metabolism. [70][71][72][73][74] However, as a substrate of the cytochromes P450, the pharmacokinetics of terbinafi ne are altered with the concurrent administration of several agents (eg, cimetidine, terfenadine, rifampin). 70,75 The clearance of terbinafi ne is triphasic with the terminal elimination half-life approximating 100 hours after a single dose and 22 days with durations of therapy spanning several months.…”
Section: Clinical Pharmacology (Tables 1 and 2)mentioning
confidence: 99%
“…P450 substrate/inhibitors were examined at concentrations reported to cause preferential inhibition of the isoform: phenacetin for CYPlA2 [23]; diethyldithiocarbamate for CYP2E1 [24]; tolbutamide for CYPZC8/9 [25]; troleandomycin [26] for CYP3A3/4. Ketoconazole was also used to inhibit CYP3A4 [27,281. Although inhibition by diethyldithiocarbamate has been taken as evidence for the involvement of CYP2E1 [24], a recent study showed that it is not selective for this isoform; at the concentrations used here, it also inhibits CYP2B6 and CYP2A6 [29].…”
Section: Human Liver Microsomesmentioning
confidence: 99%